The Navajo blanket - Kahlenberg, Mary Hunt; Berlant, Anthony; Los Angeles County Museum of Art ([New York] Praeger Publishers, Inc. in association with the Los Angeles County Museum of Art, 1972)
Given in memory of Ethel A. Tsutsui, Ph.D. and Minoru Tsutsui, Ph.D.
Catalogue of an exhibition first held at Los Angeles County Museum of Art, June 27-Aug. 27, 1972, and subsequently at other museums.
Includes bibliographical references (page 111)
Keywords: Navajo textile fabrics -- Exhibitions; Indian textile fabrics -- North America -- Exhibitions